2008
DOI: 10.1128/cvi.00420-07
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Innate Immunity in Healthy Macaca mulatta Macaques by a Single Subcutaneous Dose of GMP CpG 7909: Safety Data and Interferon-Inducible Protein-10 Kinetics for Humans and Macaques

Abstract: Following a demonstration that mouse-optimized cytosine-guanosine dinucleotide (CpG) oligodeoxynucleotides stimulated innate immune protection against intracellular pathogens, we tested the ability of CpG 7909, a primate-optimized Toll-like receptor 9 (TLR9) agonist, to stimulate rhesus macaques to produce interferon-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…In agreement with previous reports of SC administration of CPG 7909 [2;18;19] we found comparable response kinetics and magnitudes of IP-10 and IL-6 serum content after the vaccines were administered IM. These responses were transient and returned to baseline by day 7, indicating the potential to monitor repeated doses of CpG-adjuvanted vaccines for potentially unregulated activation of innate immunity by evaluating cytokine/chemokines or readily available CRP or ALC.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports of SC administration of CPG 7909 [2;18;19] we found comparable response kinetics and magnitudes of IP-10 and IL-6 serum content after the vaccines were administered IM. These responses were transient and returned to baseline by day 7, indicating the potential to monitor repeated doses of CpG-adjuvanted vaccines for potentially unregulated activation of innate immunity by evaluating cytokine/chemokines or readily available CRP or ALC.…”
Section: Discussionsupporting
confidence: 93%
“…Human serum biomarkers affected by CpG adjuvants include increased IP-10 and IL-6 [2], IL-12, MCP-1 and IFN-α [3] as well as enhanced antibody responses [1;4;5]. Also reported were transiently decreased absolute lymphocyte counts (ALC) and C-reactive Protein (CRP) after subcutaneous (SC) administration [3;6;19], in vitro interferon-gamma (IFN-γ) production by peripheral blood mononuclear cells (PBMC) obtained after in vivo CpG treatment [4], increased T cell expansion [7], increased circulating T cells and NK cells after intra-venous (IV) administration [6] and increased CD8 + T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Safety studies conducted in animals with CpG ODNs found them to be less reactogenic than other adjuvants [4244] and has led to the use and testing of CpG ODN 7909 in human clinical trials [45, 46]. Of particular relevance to our study, a mouse study assessing safety of CpG ODNs administered IM reported minimal to no tissue damage in the injected tissue [42].…”
Section: 0 Discussionmentioning
confidence: 86%
“…inoculations with intra-nasal (i.n.) immunization with the gp41t-Fc construct that could potentially induce antibodies localized to the FRT; use a TLR9 agonist and CpG adjuvant, with the rationale that TLR9 agonists have been shown to induce strong B cell responses in other settings [29] and have been used safely in rhesus macaques [30]. …”
Section: Resultsmentioning
confidence: 99%